In vitro studies on gastrointestinal monogastric and avian models to evaluate the binding efficacy of mycotoxin adsorbents by liquid chromatography-tandem mass spectrometry - Prapapanpong, Jutamas; Udomkusonsri, Pareeya; Mahavorasirikul, Wiratchanee; Choochuay, Sasiprapa; Tansakul, Natthasit (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of this study is evaluating the efficacies of 11 mycotoxin adsorbent products, marketed in South East Asia. Three prominently occurring mycotoxins; aflatoxin B1 (AFB1), deoxynivalenol (DON), and zearalenone (ZEN) were simultaneously spiked into the samples. Materials and Methods: Samples were simultaneously tested in vitro in phosphate buffer and simulated at different pH conditions in the gastrointestinal tracts of the porcine and avian model, analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: All mycotoxin adsorbent products had high efficacy at over 90% for AFB1 adsorption in both GI porcine and avian models. AFB1 could be adsorbed more in acidic condition than the basic condition. ZEN adsorption was determined to be more stable at pH 3 than pH 6.5 or 8.4, in which pH condition might influence on ZEN desorption rate. DON was poorly adsorbed by all tested agents. Conclusions: The finding showed that the adsorption rate varied depending on the type of adsorbent. Our results might provide useful information regarding the efficacy of mycotoxin adsorbents commercially marketed in the region. J. Adv. Vet. Anim. Res., 6(1): 125-132, March 2019